El intercambio académico como método de desarrollo profesional para universitarios (2014)
Academic exchange is one of the leading references on the processes and strategies of educational cooperation and, in addition to being direct expression of the collaboration between institutions and governmental structures, is also an important element of the set of educational policies in the field of internationalization of higher education and collaboration in the field of development. In this project there is a brief analytical approach to the positive and negative aspects that can have an impact both on the internationalization of higher education, such as regional integration and cooperation in general educational, highlighting the role that higher education institutions and national and international organizations play in promoting collaboration agreements that have as their ultimate goal the strengthening of what might be called further education. At the same time, is highlighted the importance of international student mobility or academic exchange as a development method for college as well as being a key to improving the training element, the exchange of knowledge and culture that allow for the solution for some problems of the citizens of the participating countries.